The Practice of Local Leadership and Governance in Nepal: A Historical Perspective - Chaudhary, Deepak; Shrestha, Chandra Lal; Sapkota, Mahendra (Historical Journal, 2023)
The paper aims to study the practice of local leadership and governance in Nepal critically. The historical perspective synthesizing the review of literature and interpretation analyzing the changes over some time is adopted as a method. The practice of local leadership and governance in Nepal has been since ancient times. The kings and states are examples of leadership and governance practice that is mentioned in Hindu and Buddhist scriptures. The great-men theory or charismatic theory of leadership has largely been associated with leadership and the governance system was mainly based on religious and community basis and ultimately utopian ideas. Self-rule was found on a community basis as governance at the local level. Similarly, the charismatic typology of leadership has long been dominant in Nepal. Despite this, leadership has largely been influenced by caste, kin, and noble family. However, with the advent of modernization, the traditional practice of governance and leadership has changed. Nonetheless, questions on leadership and governance have also been raised regarding social transformation and economic growth.